Developmental Restriction of Retrotransposition Activated in Arabidopsis by Environmental Stress. Issue 2 (3rd August 2017) - Gaubert, Hervé; Sanchez, Diego H; Drost, Hajk-Georg; Paszkowski, Jerzy
Abstract: Retrotransposons (RTs) can rapidly increase in copy number due to periodic bursts of transposition. Such bursts are mutagenic and thus potentially deleterious. However, certain transposition-induced gain-of-function or regulatory mutations may be of selective advantage. How an optimal balance between these opposing effects arises is not well characterized. Here, we studied transposition bursts of a heat-activated retrotransposon family in Arabidopsis . We recorded a high inter and intraplant variation in the number and chromosomal position of new insertions, which usually did not affect plant fertility and were equally well transmitted through male and female gametes, even though 90% of them were within active genes. We found that a highly heterogeneous distribution of these new retroelement copies result from a combination of two mechanisms, of which the first prevents multiple transposition bursts in a given somatic cell lineage that later contributes to differentiation of gametes, and the second restricts the regulatory influence of new insertions toward neighboring chromosomal DNA. As a whole, such regulatory characteristics of this family of RTs ensure its rapid but stepwise accumulation in plant populations experiencing transposition bursts accompanied by high diversity of chromosomal sites harboring new RT insertions.